Optimization of the epoxidation reaction of Calophyllum inophyllum oil-based epoxy - Suhendra, Dedy; Sudirman, Sudirman; Murniati, Murniati; Handayani, Sri Seno; Iswari, Ni Kadek Suardani; Gunawan, Erin Ryantin (Molekul, 2026)
ABSTRACT. Epoxy is synthesized through an epoxidation reaction, namely the oxidation of double bonds by active oxygen to form an oxirane ring. Generally, epoxy is synthesized from petroleum-derived raw materials which are non-renewable energy sources. Vegetable oils which contain unsaturated bonds can be used as alternative raw materials for producing epoxy. In this research, Calophyllum inophyllum oil (the local name is nyamplung), which is a non-edible and non-commercial vegetable oil, was used as a feedstock in the preparation of epoxy. Epoxidation takes place in situ, namely performic acid which reacts with nyamplung oil is produced from the reaction between HCOOH and H2O2, and is catalyzed by sulfuric acid simultaneously. The indicators in this epoxidation reaction are the oxirane oxygen content (OOC) and the relative conversion to oxirane (RCO). The optimum epoxidation conditions obtained are duration of epoxidation of 6 h, ratio of oil:HCOOH:H2O2 is 1:3:4 (mole/mole), and epoxidation temperature of 45 °C. The product was characterized using FTIR and NMR. Keywords: Calophyllum inophyllum oil; epoxidation; epoxy; oxirane oxygen content